EXAMINING TAXIS AND LOGICO-SEMANTIC RELATIONS OF CLAUSE COMPLEXES IN SPOOF - Azza Azkiya (Journalistics: Journal of English Teaching and Applied Linguistics, 2025)
This study investigates the taxis system and logico-semantic relations within clause complexes in a spoof text using the framework of Systemic Functional Linguistics (SFL) as developed by Halliday and Matthiessen. Spoof, a genre designed to amuse through unexpected twists, is examined to determine how its structure aligns with spoken or written discourse. A descriptive qualitative approach was employed, and data were drawn from a spoof text containing at least 30 clauses, selected randomly from a humor website. The analysis focused on identifying the types of clause interdependency (parataxis vs. hypotaxis) and the logico-semantic relations (expansion and projection) present. Findings reveal that paratactic relations dominate over hypotactic ones, with 65% of the clause complexes connected paratactically. This indicates a greater resemblance to spoken discourse, which contrasts with previous studies suggesting written texts typically feature more hypotaxis. In terms of logico-semantic relations, extension (as part of expansion) is the most frequent, and projection—especially locution—is used more often than idea. The frequent use of locution projection, which is more typical in spoken discourse, further supports the conclusion that spoof texts, though written, adopt structures associated with spoken language. This tendency likely stems from the genre's purpose to entertain, as simpler structures enhance readability and comprehension. These findings contribute to a better understanding of how humor texts manipulate linguistic structures to achieve communicative goals.